Lake Wobegon’s Guns: Overestimating Our Gun-Related Competences - Emily Stark; Daniel Sachau (Journal of Social and Political Psychology, 2016)
The Lake Wobegon Effect is a general tendency for people to overestimate their own abilities. In this study, the authors conducted a large, nationally-representative survey of U.S. citizens to test whether Americans overestimate their own gun-relevant personality traits, gun safety knowledge, and ability to use a gun in an emergency. The authors also tested how gun control attitudes, political identification, gender, and gun experience affect self-perceptions. Consistent with prior research on the Lake Wobegon Effect, participants overestimated their gun-related competencies. Conservatives, males, and pro-gun advocates self-enhanced somewhat more than their counterparts but this effect was primarily due to increased gun experience among these participants. These findings are important to policymakers in the area of gun use, because overconfidence in one’s gun-related abilities may lead to a reduced perceived need for gun training.